Housing prices, tenancy and external shocks: the portuguese evidence - Santos, António Duarte (2021)
When the Special Resettlement Program started in 1993, several studies pointed to the need to build about half a million houses, which was not unrelated to the existence of a huge amount of informal and precarious constructions (e.g., Guerra (1999), Cachado (2013), Alves (2016), Allegra et al. (2017), Fahra ( • In twenty years, the country has produced one and a half million new homes, closing, in technical terms, the housing deficit. • Nevertheless, there are still problems related to the degradation and increase in the construction of the housing stock in urban centers and outskirts of cities, with the mobility needs of households and with the cost of housing. • According to the OECD (2020), since 2010, Portuguese families have been the ones that most allocate the largest proportion of their income to housing costs. • It is in this context that the expression “ so many homeless people without a house and so many homeless housing ” has taken on a recent